ACM and Model Forests: A new paradigm for Africa - Diaw, M.C.; Nguièbouri, J.; N’Tambu, B.V.; Tchoko, J.G.; Ngo Baneg, M.F.R.; Bilogui, C. (Routledge, 2023)
The chapter documents ACM embeddedness in a Model Forests transformative change attempt to plant the seeds of a collaborative ecological economy in Central Africa. It introduces the forest ‘poverty paradox’ and related challenges for participatory engagements. It then highlights the ‘inversion’ of the African forest economy, criticizing the blindness of environmental ideologies and interventions to that disability and to their responsibility in maintaining conditions of African structural poverty. The chapter explains Africa’s criticality and considers future options from the ground up. The chapter’s central objective is to question and rethink the roles and ambitions of participatory engagements for local democratic governance in Africa, emphasizing the ‘poverty paradox’ and its momentous significance.